Kebijakan Pemerintah Mempertahankan BI 7-Day Reverse Repo Rate Sebesar 4,50% - Al Amin, Eka Mulia Nurul (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
The Covid-19 pandemic not only hit the health sector but also rocked a country’s economy. Nevertheless, the government has continued to set a series of policies to shore up the economy, including making more fiscal spending, providing tax relief, cutting borrowing rates and bank reserve requirements to revive an economy ravaged by the outbreak and to support jobs. This article aims to discuss the government’s monetary policy in the face of economic shocks during the Covid-19 pandemic. Especially specific in Bank Indonesia’s decision to keep interest rates on hold, which was announced at the BI Board of Governors Meeting, held on August 18-19, 2020. After analysis and discussion, it was found that this decision was made to maintain external stability amid low inflation and consider the global economy which showed signs of improvement after experiencing severe pressures in the second quarter 2020.